Answer:
[tex]\frac{1-cos^2(2x)}{4}[/tex]
Step-by-step explanation:
We have the following expression
[tex]sin^2x *cos^2x[/tex]
Whe know that:
[tex]sin^2(x) = \frac{1-cos(2x)}{2}\\\\cos^2(x)=\frac{1+cos(2x)}{2}[/tex]
Now replace these equations in the main expression and simplify
[tex](\frac{1-cos(2x)}{2})*(\frac{1+cos(2x)}{2})[/tex]
[tex](\frac{(1-cos(2x))(1+cos(2x))}{4})[/tex]
Apply the following property
[tex](a + b) (a-b) = a ^ 2 -b ^ 2[/tex]
Then
[tex](\frac{(1-cos(2x))(1+cos(2x))}{4})=\frac{1^2-cos^2(2x)}{4}[/tex]
Finally:
[tex](\frac{(1-cos(2x))(1+cos(2x))}{4})=\frac{1-cos^2(2x)}{4}[/tex]